Inclusive Education and Disability in the Global South (Springer International Publishing, 2018)
This edited volume examines inclusive education and disability in the global South. Presenting four qualitative research studies conducted in Malaysia, Bhutan, Philippines and Belize, the authors examine the implementation of inclusive education and disabled children's participation in the education system: contexts on which very little is known. Thus, this book provides a unique opportunity to access rare context-specific information concerning this region of the world; and to reflect on the particular challenges some countries face in the realization of full participation of all children within education. Authored by researchers who are also teaching professionals with experience and understanding of the complexities of the real world, this book reminds us that researchers and policy makers must listen to all voices and perspectives: especially those that have remained silenced and ignored. .